Promoting Group Creativity in Upstream Requirements Engineering - Ocker, Rosalie (Human Technology, 2010)
The upstream stage of requirements engineering (RE) focuses primarily on determining high-level organizational requirements. Upstream RE provides perhaps the best opportunity to instill creativity into the design process, since it is where stakeholders figure out what to build. However, exactly how to incorporate creativity into current RE methods remains a fundamental concern. Negative social influences, such as those associated with status differentials, ingroup bias, and majority influence, can impede group creativity and otherwise negatively impact the upstream RE process. This paper discusses these issues. Two IBIS-based design rationale approaches are presented and suggestions for diminishing the potential for negative social influences are offered.